Artificial intelligence in medicine and dermatology - Woźniacka, Anna; Patrzyk, Sebastian; Mikołajczyk, Maksym (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
As technology advances rapidly and vast amounts of data are collected, artificial intelligence (AI) is increasing its presence in our lives. Medicine is a major focus point of AI developers. There are examples of algorithms on par with medical professionals, the most prominent case being skin cancer recognition. However, advancement involves the necessity to adapt to technology and to patients utilizing it on a daily basis. What is more, patients present growing trust towards machine-aided health care. Dermatology is a potent field for AI use as visual data are easy to collect, hold a lot of information and are paramount for diagnosis.